Lifestyle-related risk factors correlated with mental health problems: A longitudinal observational study among 686 male college students in Chongqing, China - Yang, Bin-Wei; Zou, Peng; Chen, Qing; Sun, Lei; Ling, Xi; Yang, Huan; Zhou, Ni-Ya; Wang, Li-Hong; Huang, Lin-Ping; Liu, Jin-Yi; Yang, Hui-Fang; Cao, Jia; et al. (Frontiers in Public Health, 2022)
Aim: Public concerns over the mental health problems of college students are rising. This study sought to explore the association of lifestyle-related risk factors with the prevalence of mental health problems in Chinese college students. Methods: The lifestyle information and mental health status of 686 male college students from Chongqing, China, were assessed in 2014, and 582 of them were followed up a year later. Participants completed a questionnaire assessing demographic and lifestyle factors. Mental health problems were measured using the Depression Anxiety Stress Scale-21 (DASS-21). Results: Univariate analyses indicated that age, sleep latency, sleep duration, computer usage time, milk tea drinking, and fried food consumption were potential risk factors for mental health problems (p’s < 0.05). Multivariate analysis further revealed that, either at baseline or during follow-up, participants with (i) more computer usage time were at a higher risk of having depression symptoms (p’s < 0.05) and (ii) a higher frequency of fried food consumption were associated with a higher risk of having depression, anxiety, and stress symptoms (p’s < 0.05). Additionally, the cross-lagged analysis showed that (i) computer usage time in 2014 is positively correlated with depression status (β = 0.106, p < 0.05) but not anxiety (β = 0.047, p > 0.05) and stress (β = 0.019, p > 0.05) status a year later and (ii) fried food consumption in 2014 is positively correlated with depression (β = 0.129, p < 0.01), anxiety (β = 0.168, p < 0.001), and stress (β = 0.113, p < 0.01) status a year later. Conclusions: Computer usage time and fried food consumption were lifestyle-related risk factors for mental health problems in Chinese college students.